Pengaruh Model Problem-Based Learning dalam Meningkatkan Minat dan Hasil Belajar Matematika Siswa Sekolah Dasar - Asrina, Asrina; Masdin, Masdin; Halistin, Halistin (IAIN Kendari, 2024)
This study aims to analyze the influence of the Problem-Based Learning (PBL) model on the learning interest and mathematics achievement of fifth-grade students at SDS IT Asy Syamil. Using a quasi-experimental method with a Non-Equivalent Control Group Design, the study involved 36 students divided into experimental and control groups. Research instruments included validated and reliable learning achievement tests and learning interest questionnaires. The results showed significant differences in students' learning interest and achievement before and after the PBL implementation, as well as between the experimental and control groups post-treatment. These findings indicate that PBL is effective in enhancing students' active engagement and academic outcomes. The study contributes to the growing body of empirical evidence supporting PBL effectiveness in primary education, particularly in mathematics learning in Indonesia. However, limitations include the small sample size and the focus on a single school. Further research with broader populations and across different subjects is recommended.Keywords: Problem-based learning, learning interest, learning achievement, mathematics, primary education